Foster carers : why they stay and why they leave - Sinclair, Ian, 1938- (Supporting parents., 2004)
Foster care, which can include both long- and short-term placements, is the most common way in which local authorities look after other people's children. Examining the problems and the positive experiences of those providing care, Foster Carers is essential reading for social work professionals, academics and foster carers themselves. Through questionnaire responses from over a thousand foster carers across seven different local authorities, the authors highlight the importance of identifying and fulfilling appropriate kinds of care; the need to recruit and retain carers; and, finally, examin.